The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.31124/advance.9731702.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Knowledge about family and school contributions in academic achievement-The context of schooling and social representations in India.pdf

Abstract: The present paper seeks to identify the social representations of the family and school contribution in students' academic achievement. Earlier studies have taken family and school contribution in terms of taken for granted causal factors but how they are embedded in our everyday understanding and interactions may provide an alternative perspective. The qualitative methodology of content and correspondence analysis of categorical data derived from interviews and written responses from parents, teachers and stu… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…(NFHS-5) report showed that the percentage of women who had ever undergone a screening test for cervical, breast and oral cancer were 1.9%, .9% and .9%, respectively. 39 The COVID pandemic had further impacted screening practices adversely in most health centers. In a survey of 41 cancer centers in 2020, it was seen that the cancer screening practices were almost non-existent or functioning at less than 25% capacity in more than 70% of the healthcare centers.…”
Section: Management Of Gynaecologic Cancer During Covid-19-indian Sce...mentioning
confidence: 99%
“…(NFHS-5) report showed that the percentage of women who had ever undergone a screening test for cervical, breast and oral cancer were 1.9%, .9% and .9%, respectively. 39 The COVID pandemic had further impacted screening practices adversely in most health centers. In a survey of 41 cancer centers in 2020, it was seen that the cancer screening practices were almost non-existent or functioning at less than 25% capacity in more than 70% of the healthcare centers.…”
Section: Management Of Gynaecologic Cancer During Covid-19-indian Sce...mentioning
confidence: 99%